A facile, green and efficient surfactant-free method for synthesis of aluminum nanooxides with an extraordinary high surface area. Issue 15 (14th March 2016) - Mohammadnezhad, Gholamhossein; Akintola, Oluseun; Plass, Winfried; Steiniger, Frank; Westermann, Martin
Abstract : Nano boehmite with unprecedented high surface area and pore volume (802 m 2 g −1, 2.35 cm 3 g −1 ) was prepared using a facile, green and efficient surfactant-free synthesis method. Abstract : Nano boehmite with unprecedented high surface area and pore volume (802 m 2 g −1, 2.35 cm 3 g −1 ) was prepared using a facile, green and efficient surfactant-free synthesis method. The structure of the material is characterized by the presence of plates with varying thicknesses and morphologies. The calcined samples show curved and rolled plates with a nanotube-like appearance.